Memory, Plasticity and Sleep - A role for calcium permeable AMPA receptors? - Shepherd, Jason D. (Frontiers in Molecular Neuroscience, 2012)
Experience shapes and molds the brain throughout life. These changes in neuronal circuits are produced by a myriad of molecular and cellular processes. Simplistically, circuits are modified through changes in neurotransmitter release or through neurotransmitter detection at synapses. The predominant neurotransmitter receptor in excitatory transmission, the AMPA-type glutamate receptor, is exquisitely sensitive to changes in experience and synaptic activity. These ion channels are usually impermeable to calcium, a property conferred by the GluA2 subunit. However, GluA2-lacking AMPARs are permeable to calcium and have recently been shown to play a unique role in synaptic function. In this review, I will describe new findings on the role of calcium permeable AMPARs (CP-AMPARs) in experience-dependent and synaptic plasticity. These studies suggest that CP-AMPARs play a prominent role in maintaining circuits in a labile state where further plasticity can occur, thus promoting metaplasticity. Moreover, the abnormal expression of CP-AMPARs has been implicated in drug addiction and memory disorders and thus may be a novel therapeutic target.